The Impact of an Environmentally Friendly Human Resource on Improving the Environment and Reducing Costs - Ashwaq T.Kadhim (Journal of Madenat Alelem University College, 2020)
Concerns in the environmental issues of depletion of resources, reduction of biodiversity and the emergence of concerns among individuals in green management, despite concerns, are responsible for ensuring environmental sustainability and how to improve them. Therefore, the research problem is the extent to which the environmentally friendly human resource contributes to improving the environment and reducing costs. The research aims to achieve a number of objectives that highlight the concept of human resource objectives and functions in addition to the concept of human resource friendly to the environment and its importance and dimensions. The most important findings of the study that the human resource is two elements of the human resource Environment and the preservation of knowledge capital and is the cornerstone of any business, both on the level of sustainable business or financial and are responsible for the planning and implementation of environmentally friendly policies and without them will be sustainable and difficult green and difficult and based on the above, the most recommended by the study to adopt the policies and functions of the supplier Environment-friendly environment that works towards the sustainability of the environment by directing workers to use the resource available to the economic unit in a positive manner in addition to implementing policies and laws related to environmental safety.